INTERVIEWING A ROBOT: Notes on the experimental application of the EEAF methodology using the ChatGPT artificial intelligence tool. (Comunicação & Inovação, 2023)
It presents the methodology EEAF - Exploratory Interview for the Evaluation of Functionalities - to be used by Communication researchers, in the study of characteristics or analysis of textual material, created by artificial intelligence algorithms. In this work we use the ChatGPT conversation tool and propose a set of metrics: transparency, structuring, precision, variety and updating, for evaluation in the experiment. In general, texts created via code showed the need for human review, especially in materials that dealt with objective facts and data.
Keywords: Artificial Inteligence; CHATGPT; Natural Language Processing